Comprehensive analysis of the effect of Hashimoto’s thyroiditis on the diagnostic efficacy of preoperative ultrasonography on cervical lymph node lesions in papillary thyroid cancer - Hai-Long Tan; AdolphusOsei Nyarko; Sai-li Duan; Ya-Xin Zhao; Pei Chen; Qiao He; Zhe-Jia Zhang; Shi Chang; Shi Chang; Shi Chang; Shi Chang; Peng Huang (Frontiers in Endocrinology, 2023)
PurposeHashimoto’s thyroiditis often leads to reactive hyperplasia of the central compartment lymph nodes in papillary thyroid carcinoma (PTC) patients. However, the effect and clinical significance of Hashimoto’s thyroiditis (HT) on ultrasonography evaluation for cervical lymph node (LN) lesions remain unknown. This study aims to investigate the effect of Hashimoto’s thyroiditis on the diagnostic efficacy of preoperative ultrasonography on cervical lymph node lesions in PTC patients.Patients and methodsThis study consecutively enrolled 1,874 PTC patients who underwent total thyroidectomy and radical cervical lymph node dissection between January 2010 and December 2021. Eligible patients were categorized as with HT and without HT. The diagnostic performance of preoperative ultrasonography for cervical LN lesions (including central LNs and lateral LNs) was evaluated between PTC patients with HT and those without HT, respectively.ResultsAmong the 1,874 PTC patients, 790 (42.1%) had central cN+ and 1,610 (85.9%) had lateral cN+. Compared with PTC patients without HT, the preoperative US for central LNs displays a higher false-positive rate (27.9% vs. 12.2%, p <0.001) and a lower specificity (72.1% vs. 87.8%, p < 0.001) in PTC patients with HT. Moreover, in PTC patients with HT, the ratio of the absence of fatty hilum in central LNs without metastasis was higher than in PTC patients without HT (13.02% vs. 7.46%, p = 0.013). However, no such differences were observed in lateral LNs.ConclusionHT will interfere with the preoperative US evaluation for central LNs and increase the incidence of the absence of fatty hilum in central benign LNs. When PTC patients have concomitant HT, clinicians should thoroughly evaluate the central LNs, thereby decreasing the incidence of misdiagnosis and unnecessary surgery.